Intra-operative Intravitreal Bevacizumab For Patients With Diabetic Macular Edema Undergoing Phacoemulsification with Foldable IOL Implantation - Haider Ali Chaudhry; Gulnaz; Irfan Ahmed Sualeh; Muhammad Ahmad (Aziz Fatimah Medical and Dental College, 2024)
Objective: To assess the efficacy of Intra-operative Intravitreal Bevacizumab in treating Diabetic Macular Edema in patients undergoing Phacoemulsification with Foldable intraocular lens (IOL) Implantation, in comparison to a control group. Methodology: This experimental study was performed in department of Ophthalmology, Madinah Teaching Hospital, Faisalabad from 5th October to 2022 - 5th March 2023. Sixty patients (30 in each group) were enrolled in the study. Patients in group "A" received Intravitreal Bevacizumab immediately after phacoemulsification with foldable IOL implantation.Whereas Intravitreal Bevacizumab was not given to patients in group B (control group). Best Corrected Visual Acuity (BCVA) and macular thickness using optical coherence tomography (OCT) were recorded within a timeframe of 7-30 days prior to surgery, as well as at 1 and 3 months after the surgery for comparison between the two study groups. Results: The study comprised 60 patients, with a mean age of 56.43 ± 5.90 years, representing both genders. Among the participants, males were predominant, accounting for 32 (53.3%) individuals, while females constituted 28 (46.7%) of the sample. The baseline best-corrected visual acuity (BCVA) measurements between group A and group B were 0.22 ± 0.68 and 0.21 ± 0.07, respectively. There was no statistically significant difference observed between the two groups (P = 0.677). However, significant disparities in BCVA were observed after one- and three-months post-surgery, favoring group A.Similarly, mean optical coherence tomography (OCT) at baseline was 271.09 ± 26.87 in group A and 307.57 ± 32.81 in group B, with no significant difference (P = 0.771). Nonetheless, significant differences in OCT were noted after one- and three-months post-surgery, with group A demonstrating superior results. These findings underscore the beneficial impact of intra-operative Bevacizumab in improving both BCVA and OCT outcomes post-surgery. Conclusion: The administration of intravitreal bevacizumab during phacoemulsification has been shown to yield notable improvements in Best Corrected Visual Acuity (BVCA) and Optical Coherence Tomography (OCT) among those with diabetes with macular edema who are undergoing cataract surgery.